2020
DOI: 10.1088/1361-6463/ab7c97
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of particle charging in low-temperature, atmospheric-pressure, flow-through plasmas

Abstract: While plasmas are now routinely employed to synthesize or remove nano- to micron-sized particles, the charge state (polarity and magnitude) of the particles remains relatively unknown. In this study, charging of nanoparticles was systematically characterized in low-temperature, atmospheric-pressure, flow-through plasmas previously applied for synthesis. Premade, charge-neutral nanoparticles of MgSO4, NaCl, and sea salt were introduced into the plasma to decouple other effects such as the reactive vapor precurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 48 publications
(71 reference statements)
2
43
0
Order By: Relevance
“…Figure 1c shows the charge distribution on MgSO 4 particles with 25 and 45 nm mean mobility diameters exiting the plasmas at two different DC voltages. At a DC voltage of 0 kV, the particles exhibit a bipolar charge distribution, which can be attributed to a two-stage charging mechanism in the plasma reactor that was previously reported (Sharma et al 2020). Briefly, particles first acquire a predominantly negative charge in the plasma volume and subsequently, in the spatial afterglow, electrons are lost faster to the walls as compared to the positive ions because of their higher mobility, resulting in a larger flux of positive ions to the particles and neutralization.…”
Section: Charging Characteristicssupporting
confidence: 55%
See 4 more Smart Citations
“…Figure 1c shows the charge distribution on MgSO 4 particles with 25 and 45 nm mean mobility diameters exiting the plasmas at two different DC voltages. At a DC voltage of 0 kV, the particles exhibit a bipolar charge distribution, which can be attributed to a two-stage charging mechanism in the plasma reactor that was previously reported (Sharma et al 2020). Briefly, particles first acquire a predominantly negative charge in the plasma volume and subsequently, in the spatial afterglow, electrons are lost faster to the walls as compared to the positive ions because of their higher mobility, resulting in a larger flux of positive ions to the particles and neutralization.…”
Section: Charging Characteristicssupporting
confidence: 55%
“…We chose the 40 nm mobility diameter particles as a representative size to estimate the ion attachment coefficient. Sharma et al (2020) reported the ion density in the same RF, flow-through, atmospheric-pressure plasma to be about 10 20 m À3 . The ion concentration in the spatial afterglow should be several orders of magnitude lower due to wall losses and electron-ion concentration recombination.…”
Section: Characteristic Time Scale Analysismentioning
confidence: 96%
See 3 more Smart Citations